Masjid Sultan Muhammad Salahuddin Bima; Arsitektur, Misi Agama dan Kekuasaan - Retno Kartini (Jurnal Lektur Keagamaan, 2017)
The article discusses the history of Sultan Muhammad Salahuddin Mosque in Bima, and it was written as an effort to preserve the cultural heritage of the Indonesian heritage, especially related to the historic mosque and its role in the development of Islam in the region of Bima, West Nusa Tenggara. This descriptive study focuses on writing about the history of the mosque's founding, its architecture and its historic objects inside the mosque, as well as the function of the mosque from time to time. The results were extracted from various sources, starting with interviews with key informants, document studies, and observations. This historic mosque was originally built by Sultan Abdul Kadim in 1737 AD, then continued by his successor, Sultan Abdul Hamid until it was completed in 1780 AD. This palace mosque is a symbol of the religiosity of the community of Bima and serves as a center of Islamic religious mission in his time. The mosque that was destroyed by an allied bomb in 1948 was then rebuilt from its original form and was named as Sultan Muhammad Salahuddin Mosque. Artikel hasil penelitian terhadap Masjid Sultan Muhammad Salahuddin Bima ditulis sebagai salah satu upaya untuk melestarikan warisan budaya Bangsa Indonesia, khususnya yang berkaitan dengan masjid bersejarah dan perannya dalam perkembangan Islam di wilayah Bima, Nusa Tenggara Barat. Penelitian diskriptif ini berfokus pada penulisan seputar sejarah pendirian masjid, arsitektur dan benda-benda bersejarah yang ada di dalamnya, serta fungsi masjid dari masa ke masa. Hasil penelitian digali dari berbagai sumber, dimulai dengan wawancara dengan informan kunci, studi  dokumen, dan observasi. Masjid bersejarah ini awalnya dibangun oleh Sultan Abdul Kadim pada pada tanggal tahun 1737 M, kemudian dilanjutkan penerusnya, Sultan Abdul Hamid sampai selesai pada tahun 1780 M. Masjid istana ini merupakan simbol religiusitas masyarakat Bima dan berfungsi sebagai pusat penyiaran agama Islam di masanya. Masjid yang pernah hancur terkena bom tentara sekutu pada tahun 1948 kemudian dibangun kembali sesuai bentuk aslinya dan dinamai sebagai Masjid Sultan Muhammad Salahuddin.Kata kunci: Masjid bersejarah; Sultan Muhammad Salahuddin; Bima